Exploring Stunting in South Kalimantan Province Using R Programming-Based Data Visualization - Hudaya, Muhammad; Nor, Wahyudin; Yuliastina, Mellani; Nordiansyah, Muhammad (Kesmas, 2025)
South Kalimantan Province continues to face the challenge of relatively high stunting prevalence despite being endowed with abundant coal resources that could serve as a source of funding for public health. Therefore, this study aimed to examine differences in stunting prevalence among cities, mining districts, and non-mining districts in South Kalimantan to raise stakeholder awareness of disparities across these regional types. This study was conducted between April and December 2024, using secondary data obtained from the Indonesian Ministry of Health and the South Kalimantan Provincial Government. R programming was used to process the data, generate visualizations, and perform analysis of variance (ANOVA) and Tukey’s honestly significant difference (HSD) tests. Following the significant ANOVA result, Tukey’s HSD test was conducted to identify specific regional pairs that differed significantly following the ANOVA result. The results showed that cities had significantly lower mean stunting prevalence than non-mining districts (p-value0.05). Additionally, no significant difference was observed between mining and non-mining districts (p-value >0.05). In conclusion, abundant coal resources in mining districts have not translated into more effective stunting reduction efforts.